2015
DOI: 10.1128/microbiolspec.iol5-0006-2015
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases at High Altitude

Abstract: Travel to elevations above 2,500 m is an increasingly common activity undertaken by a diverse population of individuals. These may be trekkers, climbers, miners in high-altitude sites in South America, and more recently, soldiers deployed for high-altitude duty in remote areas of the world. What is also being increasingly recognized is the plight of the millions of pilgrims, many with comorbidities, who annually ascend to high-altitude sacred areas. There are also 400 million people who reside permanently in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…High altitude surgical procedures constitute a unique challenge due to the hypoxic environment in which they are performed, which may lead to several postoperative consequences. Within this oxygen-depleted environment, a patient's oxygen-saturation curve is altered, and saturation percentages are decreased rendering patients more susceptible to systemic infection 6 7 8) . A literature review found little detail regarding the effect of high altitudes on postoperative infections in primary THA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High altitude surgical procedures constitute a unique challenge due to the hypoxic environment in which they are performed, which may lead to several postoperative consequences. Within this oxygen-depleted environment, a patient's oxygen-saturation curve is altered, and saturation percentages are decreased rendering patients more susceptible to systemic infection 6 7 8) . A literature review found little detail regarding the effect of high altitudes on postoperative infections in primary THA.…”
Section: Discussionmentioning
confidence: 99%
“…With a decrease in the partial pressure of oxygen at higher altitudes, systemic variations in the oxygen-hemoglobin curve and oxygen saturation percentages can lead to a state of constant endothelial cell damage and repair 2 3 4 5) . Higher altitudes also alter immune responses, therefore potentially creating an immunosuppressive environment for patients 6) . The hypoxic environment, paired with the various systemic physiological changes associated with higher altitudes, can lead to an increased susceptibility to infectious pathogens postoperatively 6 7 8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the molecular mechanisms that enable high-altitude adaptation in mammals of the plateau is important for preventing and treating hypoxia and related diseases [ 2 , 3 , 12 , 17 , 19 , 25 ]. The yak, an essential animal in Tibet, provides food, shelter, fuel, and transport for the local people, largely due to its ability to adapt to cold, low-oxygen, and low-atmospheric pressure environments.…”
Section: Discussionmentioning
confidence: 99%
“…When considering metabolic and respiratory disease in the context of oxygen supply at altitude, it is of further intrigue to note that while there is evidence of increased susceptibility to some infections at high altitude [210], those living at and adapted to high altitude (Andeans and Tibetans) may be less likely to develop severe adverse respiratory dysfunction during other infections, such as SARS-CoV-2 (COVID-19) [211]. Given that the innate and adaptive immune responses are subject to modulation by hypoxia [212], it is significant that they can be modulated by AMPK, in addition to HIFs-α, in either a beneficial or detrimental way depending on the nature of infection [213].…”
Section: Pathological Links Between Ampk Oxygen Supply and Food Choicementioning
confidence: 99%